2022
DOI: 10.1101/2022.01.29.478341
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A lymphatic-stem cell interactome regulates intestinal stem cell activity

Abstract: Barrier epithelia depend on resident stem cells for homeostasis, defense and repair. Intestinal stem cells (ISCs) of the small and large intestines respond to their local microenvironments (niches) to fulfill a continuous demand for tissue turnover, yet the complexity of their niches is still unfolding. Here, we report an extensive lymphatic network that intimately associates with ISCs within these niches. Devising a lymphatic:organoid coculture system, we show that lymphatic-secreted factors maintain ISCs whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 83 publications
(110 reference statements)
1
9
0
Order By: Relevance
“…Thus, FOXC1 and FOXC2 are likely to regulate RSPO3 expression directly in LECs. During our manuscript preparation, others have submitted bioRxiv preprints 56,57,58 showing that RSPO3 produced by intestinal LECs is required for maintaining ISCs in homeostasis and regeneration, reinforcing our finding that FOXC transcription factors mediate LEC-derived RSPO3 expression as a critical paracrine regulator in intestinal regeneration after I/R injury 59 .…”
Section: Discussionsupporting
confidence: 72%
“…Thus, FOXC1 and FOXC2 are likely to regulate RSPO3 expression directly in LECs. During our manuscript preparation, others have submitted bioRxiv preprints 56,57,58 showing that RSPO3 produced by intestinal LECs is required for maintaining ISCs in homeostasis and regeneration, reinforcing our finding that FOXC transcription factors mediate LEC-derived RSPO3 expression as a critical paracrine regulator in intestinal regeneration after I/R injury 59 .…”
Section: Discussionsupporting
confidence: 72%
“…Among IP1 ligands were the ephrins EPHB3, whose expression gradient is known to control ISC differentiation 47 , and RSPO3 ( Figure 4E ). Two recent studies have each reported that RSPO3 production by lymphatic endothelial cells (LECs) and GREM1 + fibroblasts is critical for maintaining the ISC niche in mice 45,46 . In this human dataset, we did not observe expression of RSPO3 in LECs ( Supplementary Figure 3 ); however, we did find that GREM1 + fibroblasts expressed RSPO3 as a part of IP1 that was predicted to be sensed primarily by ISCs, thus demonstrating that this interaction pathway may communicate between different cell types in mouse than in human ( Figure 4D-F ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the absence of RSPO3 expression in LECs, it remains possible that LECs maintain the ISC niche in human intestinal development, particularly as these cells can reside in close spatial proximity to ISCs 45,46 . We were able to identify a small population of LECs ( Figure 4H ), and we examined CCC between LECs and ISCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations